Study of Efficacy of Disinfecting Effects of the Deconex 50 AF And Glutaraldehyd on Bacteria Isolated From Surgical Room Of Hospitals of Hamadan - R Yousefi Mashouf; M Nazari (Tehran University of Medical Sciences, 2007)
Background: Nosocomial infection is one of the most important and problematic difficult in the educational hospital. There are different points of view about applying of disinfectant material in surgical rooms. According to the both side effect and health care financial, selecting the best material to disinfections is important. Therefore this study has been done to determine of effects of two material including Cidex (glutaraldehyd) and Deconex 50 AF (ammonium quaternary compounds). Methods: In this study 460 samples were collected randomizing from surgical rooms of Mobasher Kashany and Imam Khomeini hospitals of Hamadan. The samples were taken from surfaces and surgical instrument. The first group was the samples that were taken before and after applying Glutaraldehyd. In this group there were 110 samples befor and 110 after doing disinfections. The second group was the samples that were taken before and after applying Deconex 50 AF. The numbers of samples were 120 before and 120 after doing disinfections. There were five days interval between each stage of sampling in this period, the surgical room was active after selecting and the samples were cultured on the specific media and transferred to lab. Then the data were analyzed and compared by SPSS program by computer. Results: The most important bacteria isolated were as follow: Bacillus subtilis, Staphylococcus epidermidis, Enterobacter aeroginosa, Corynebacterium diphteroides and E. coli. This study also indicated that the efficacy of the two solution were significantly different (P= 0.04) before and after disinfections. The disinfections effect of Deconex 50 AF was 73% and Glutaraldehyde was 59%. Acording to the ranking of efficacy, the first is Deconex 50 AF and the second is Glutaraldehyde. Conclusion: Our results showed that Deconex 50 AF was relatively more effective than Glutaradlehyde and also it has less side effect rather than Glutaradlehyde.